Automatic flour sieving machine / Muhamad Haikal Aiman Mohamad Rashidi , Noor Hafiz Noordin and Mohd Ghazali Mohd Hamami - Mohamad Rashidi, Muhamad Haikal Aiman; Noordin, Noor Hafiz; Mohd Hamami, Mohd Ghazali (School of Mechanical Engineering, 2023)
The traditional manual sieving method is known for being time-consuming and requiring a significant amount of manual labour. Moreover, it often results in inconsistent flour particle sizes, which can have a detrimental impact on the quality of the flour. To address these challenges, this study proposes the development of an automatic flour sieving machine. The automatic flour sieving machine incorporates mechanical sifting principles along with modern technology to achieve uniform and consistent flour sifting with minimal human intervention. This proposal outlines the design and development of the automatic flour sieving machine, which aims to accurately sift flour to meet specific particle size requirements. The machine will be user-friendly, easy to operate, and low maintenance. It will also have the capability to handle a wide range of flour types and particle size requirements, making it a versatile tool for the bakery and food processing industry. In conclusion, this automatic flour sieving machine has the potential to be a valuable innovation for small bakeries and food processing industries (SMEs) as it can improve the efficiency and consistency of flour sifting